Advances in phenylboronic acid-based closed-loop smart drug delivery system for diabetic therapy - Huang, Qiao; Wang, Li; Yu, Haojie; Ur-Rahman, Kaleem (Journal of controlled release, 2019)
There are many patients with diabetes in the world and the treatment of diabetes is still a hectic problem, which has a nagative impact on the life of diabetic patients. A lot of research has been done on this, among which the phenylboronic acid-based smart drug delivery system mimics the working mode of human islets. When it is injected into the human body, it automatically releases the corresponding amount of insulin according to the blood glucose level of the human body. Such drug delivery systems can be divided into gels, micelles, capsules and vesicles, etc. according to the microstructure. This paper mainly highlights the recent progress in this field. [Display omitted]